2004
DOI: 10.1159/000075139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Serum Concentrations of Total Homocysteine, Folate, Vitamin B<sub>12</sub>, and Nitric Oxide in Pregnancy: A Preliminary Study

Abstract: Objective: Nitric oxide (NO) is a potent vasodilator released by endothelial cells that plays an important role in modulating maternal and fetal vascular tone in normal pregnancy. Lower plasma levels of vitamins may result in hyperhomocysteinemia, a known risk factor in pregnancy. The aim of this study was to investigate whether there are alterations in the serum levels of total homocysteine (tHcy), folate, vitamin B12, and total nitrite, as an index of NO, in smoking as compared with age-matched no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
5
28
0
1
Order By: Relevance
“…Moreover, it provides support for studies suggesting that hyperhomocysteinemia may play an etiologic role (Knott et al, 2003; Ozerol et al, 2004; Rubini et al, 2005b; Verkleij-Hagoort et al, 2007; Wong et al, 1999). Notably, we interrogated only a subset of the genes in the folate and related pathways and there are other genes in this complex set of pathways that were not addressed in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, it provides support for studies suggesting that hyperhomocysteinemia may play an etiologic role (Knott et al, 2003; Ozerol et al, 2004; Rubini et al, 2005b; Verkleij-Hagoort et al, 2007; Wong et al, 1999). Notably, we interrogated only a subset of the genes in the folate and related pathways and there are other genes in this complex set of pathways that were not addressed in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Smoking has been implicated as a risk factor and been shown to lower the levels of folic acid and increase homocysteine (Jauniaux et al, 2007; Ozerol et al, 2004). Elevated levels of homocysteine and its conversion to homocysteine-thiolactone have been suspected of contributing to the post-translational modification of the folate receptors (Jakubowski et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that other lifestyle factors such as smoking, caffeine intake and physical activity might also affect the circulating total homocysteine (tHcy) levels (Refsum, Nurk, Smith, et al, 2006;Ozerol, E., Ozerol, I., Gökdeniz, et al, 2004;Vollset, Refsum, Irgens, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Women who smoke cigarettes during pregnancy have been shown to have lower serum folate levels than pregnant women who do not smoke cigarettes (3234). Thus, it is reasonable to postulate that folate deficiency may be related to the risk of smoking-related adverse effects on the developing embryo/fetus.…”
Section: Discussionmentioning
confidence: 99%
“…An association exists between maternal smoking and decreased folate levels (3234) and may underlie the increased risk of smoking-induced low birth weight. Compounding this risk is the fact that poor nutrition and decreases in dietary intake of folate-rich fruits and vegetables are common in smokers, or spouses of smokers (35).…”
Section: Introductionmentioning
confidence: 99%